ANALISIS DETERMINAN TERHADAP PERSISTENSI LABA PADA PERUSAHAAN JASA DI BEI - Feni Marnilin; J.M.V. Mulyadi; Darmansyah , (Media Riset Akuntansi, Auditing & Informasi, 2015)
This research to know determinant analysis of earnings persistence in the service company's (trade service and investment sectors) on the Indonesia stock exchange (idx) either partially or simultaneous. The samples used in the study using a purposive sampling methods i.e. financial statements services company's annual Trade in services and Investment in 2010 to 2014 as many as 27 of the company.The results of this study indicate that the variable cash Flow operating, the difference between the accounting Profit with Profit fiscal, Debt Levels and the simultaneous effect on Persistence. While partially cash flow operating of effect variables significantly to the Persistence of profit, variable is the difference between Accounting Profit with Fiscal Earnings do not affect significantly to earnings, and Persistence for variable Rate Debt is effect significantly to Earnings Persistence.Keyword: Cash Flow Operating, The difference between the Accounting Profit with Profit Fiscal, Debt Levels and Earnings Persistence.